Oxidative stress, NF-κB signaling, NLRP3 inflammasome, and caspase apoptotic pathways are activated in mammary gland of ketotic Holstein cows - Sun, Xudong; Tang, Yan; Jiang, Chunhui; Luo, Shengbin; Jia, Hongdou; Xu, Qiushi; Zhao, Chenxu; Liang, Yusheng; Cao, Zhijun; Shao, Guang; Loor, Juan J.; Xu, Chuang (Journal of dairy science, 2021)
Ketosis is a serious metabolic disorder characterized by systemic and hepatic oxidative stress, inflammation, and apoptosis, as well as reduced milk yield. Because of the paucity of data on mammary responses during ketosis, the aim of this study was to evaluate alterations in oxidative stress, NF-κB signaling, NLRP3 inflammasome, and caspase apoptotic pathways in mammary gland of dairy cows with ketosis. Blood, mammary gland tissue, and milk samples were collected from healthy cows [Control, blood concentration of β-hydroxybutyrate (BHB) <0.6 mM, n = 10] and cows with subclinical ketosis (SCK, blood concentration of BHB >1.2 mM and <3 mM, n = 10) or clinical ketosis (CK, blood concentration of BHB >3 mM, n = 10) at median 8 d in milk (range = 6–12). Compared with Control, serum concentration of glucose was lower (3.91 vs. 2.86 or 2.12 mM) in cows with SCK or CK, whereas concentrations of fatty acids (0.25 vs. 0.57 or 1.09 mM) and BHB (0.42 vs. 1.81 or 3.85 mM) were greater. Compared with Control, the percentage of milk fat was greater in cows with SCK or CK. In contrast, the percentage of milk protein was lower in cows with SCK or CK. We detected no differences in milk lactose content across groups. Compared with Control, activities of glutathione peroxidase, superoxide dismutase, and catalase were lower in mammary gland tissue of cows with SCK or CK. In contrast, concentrations of hydrogen peroxide and malondialdehyde were greater in cows with SCK or CK. Compared with Control, mRNA abundances of TNFA, IL6, and IL1B were greater in mammary tissues of cows with SCK or CK. In addition, activity of IKKβ and the ratio of phosphorylated inhibitor of κBα to IκBα, and of phosphorylated NF-κB p65 to NF-κB p65, were also greater in mammary tissues of cows with SCK or CK. Subclinical or clinical ketosis also led to greater activity of caspase 1 and protein abundance of caspase 1, NLRP3, Bax, caspase 3, and caspase 9. In contrast, abundance of the antiapoptotic protein was lower in SCK or CK cows. The data indicate that the mammary gland of SKC or CK cows undergoes severe oxidative stress, inflammation, and cell death.